The Effectiveness of SQ3R Method to Teach Reading Comprehension at Second Semester in Universitas Bhinneka PGRI Academic year 2024/2025 - Winanti, Estu; Kartikawati, Dina (EduCurio: Education Curiosity, 2025)
This study aims to determine the effectiveness of the SQ3R method (Survey, Question, Read, Recite, Review) in improving students' reading comprehension. This research used quantitative method with pre-experimental design in the form of one group pre-test and post-test design. The population in this study were students of English education study program of Universitas Bhinneka PGRI. The research sample amounted to 23 students who were selected through purposive sampling technique. The instruments used were pre-test and post-test. The data were collected through tests and analyzed using the paired sample t-test parametric statistical test to determine the difference in scores before and after treatment. The results of data analysis showed a significant improvement in students' reading comprehension. The pre-test mean score was 59.13, while the post-test mean score increased to 87.17, with a difference of 28.04. The significance value of <0.001 obtained from the paired sample t-test shows that there is a statistically significant difference before and after the treatment. Thus, it can be concluded that the SQ3R method is effective in improving students' reading comprehension.